Slang in animated cartoons: Translation peculiarities - Kateryna Bondarenko (LingBaW)
The research focuses on analysing the function of slang in modern cartoons (Madagascar 2, Kung Fu Panda, Shrek, Open Season, Cars) as well as translation strategies used to convey accurate meaning. Our data from film scripts (163 examples containing slang terms) has proved that slang, as an important part of cartoons’ verbal component, should be and mainly retained in translation. Excerpts from original cartoons scripts show slang use, that may function both for the protagonists’ characterisation and for the mapping of humor (carnivalesque) world picture. Componential analysis of meaning – breaking down the sense of slang terms into their minimal distinctive features – was used to determine the meaning of lexemes and reconstruct semantic domains actively verbalised by slang.